PENGARUH PENDEKATAN MATEMATIKA REALISTIK UNTUK MENGATASI MISKONSEPSI MATEMATIKA SISWA - Lisda Lubis; Ahmad Nizar Rangkuti; Suparni (LPPM-Universitas Batam, 2024)
Teachers and students alike must avoid misconceptions when studying. The actual condition shows that there are still many students who still experience misconceptions, one of which is about mathematics. But in reality it shows that there are still many students who still experience wrong concepts, one of which is regarding learning mathematics. With the ultimate aim of addressing these issues and making classroom learning more effective, Practical Science Training (RME) is used for the learning approach. The purpose of this study was to develop teaching materials using the PMRI method and assess whether the RME method worked to eliminate students' mathematical misconceptions about fractions. The purpose of this study was to see whether students' misconceptions about fraction material in Class III SD Negeri 100316 Pargarutan Julu could be corrected through learning mathematics. The population in this study amounted to 42 people. Qualitative data analysis was used in conjunction with observation, interviews, questionnaires, administration of achievement tests, and discussions with subject teachers for data collection. The results showed that (1) in the first cycle the application of Realistic Mathematics Learning increased to 70.55% which was classified as sufficient and (2) in the second cycle it increased to 85.60% which was classified as satisfactory. The conclusion of the study was that third grade students at SD Negeri 100316 Pargarutan Julu increased the material for fractional operations in Realistic Mathematics Learning.